Water chemistry and greenhouse gas concentrations in waterbodies of a thawing permafrost peatland complex in northern Norway - J. K. Knutson; F. Clayer; P. Dörsch; P. Dörsch; S. Westermann; S. Westermann; H. A. de Wit; H. A. de Wit (Biogeosciences)
Thermokarst ponds in thawing permafrost landscapes play a considerable role in greenhouse gas (GHG) emissions despite their small size, yet they remain underrepresented in Earth system models. Transitions from hydrologically isolated thermokarst ponds in peat plateaus to connected wetlands can substantially alter GHG dynamics. However, the processes and GHG impacts of these shifts are not well understood, particularly in the sporadic permafrost zones of Fennoscandia. To address this, we investigated water chemistry, dissolved organic matter (DOM) processing, and GHG fluxes over two years at the Iškoras site in northern Norway, where a degrading peat plateau includes both thermokarst ponds and an adjacent wetland stream. Thermokarst ponds exhibited low pH, high organic acidity, high oversaturation of dissolved carbon dioxide (CO2), and, especially, high concentrations of dissolved methane (CH4). The adjacent wetland stream, however, with near-neutral pH, showed lower CH4 concentrations and organic acidity but significantly higher CO2 emissions, despite moderate saturations driven by turbulence and bicarbonate replenishment. By contrast, CO2 emissions in ponds were primarily linked to DOM mineralization. Despite differences in chemistry, DOM mineralization rates were similar between ponds and the stream sites, suggesting that environmental factors like pH and microbial community differences counteract DOM lability variations. As permafrost decays and transitions from peat plateaus to wetlands, ponds as hotspots of CH4 emissions will disappear. However, total GHG fluxes across the peatland–wetland continuum will depend on wetland emissions, where CH4 emissions are usually considerable, and the fate of organic matter within the plateau. Lateral DOM fluxes may represent a significant loss of soil organic carbon (OC), highlighting the importance of hydrological connectivity in linking terrestrial and aquatic systems. This study emphasizes the need to account for the relationship between hydrological and chemical processes when assessing C and GHG fluxes in permafrost-impacted regions.